Case Study Of The Use Of Google Classroom Apps By Teachers At SDIT Mathlaul Anwar - Vania, Alexandria Sarah; Alfitriyani, Nisa; Ramadanti, Radinda Iznur; Permatasari, Yulianti; Sutisna, M Ridwan (Jurnal Ilmu Sosial Mamangan, 2025)
This study aims to evaluate the implementation of Google Classroom in learning at SD Mathlaul Anwar and its impact on student engagement, ease of managing learning, and student learning outcomes. Google Classroom, as an online learning management platform, enables more effective interaction between teachers and students, as well as facilitates the management of materials and assignments. This research uses a descriptive qualitative approach, with data collection through literature review, interviews with fifth-grade teachers, and observations of the platform's implementation in learning. The results show that Google Classroom provides significant benefits, such as easy access to learning materials, increased student participation, and efficient class management. Features such as online assignment submission, automatic reminders, and discussion rooms enable a more structured and collaborative learning process. However, the main challenges faced are the dependence on stable internet access and adequate devices. Nevertheless, these challenges can be overcome with training sessions for students and parents. This study concludes that Google Classroom can improve student learning outcomes, provide space for independent learning, and contribute to the creation of a more interactive and collaborative learning environment. The future use of Google Classroom is expected to be further optimized to support both face-to-face and remote learning with the development of new features that support project-based and interactive video learning.